What Do the General Public Know about Infertility and Its Treatment? - Lewis Nancarrow; Anuthi Fernando; Lucy Hampton; Courtney Murray; Dharani K. Hapangama; Nicola Tempest (MDPI AG, 2024)
Rates of infertility are rising, and informed decision making is an essential part of reproductive life planning with the knowledge that ART success decreases dramatically while a woman's age increases and that high costs can often be incurred during fertility treatment. We aimed to determine the current knowledge of infertility and its treatments in the general public through an online survey. We received 360 complete responses. The average age of respondents was 35 years with most respondents being female (90%), heterosexual (88%), white (85%) and university educated (79%). Of the total, 49% had children and 23% had a condition that affects their fertility; 41% had concerns about future fertility and 78% knew someone who had had fertility treatment. Participants' understanding of basic reproductive biology and causes of infertility varied with correct responses to questions ranging from 44% to 93%. Understanding of IVF outcomes was poorer with only 32% to 55% of responses being correct, and 76% of respondents felt that their education in fertility was inadequate. This survey highlights the inconsistencies in the general public's understanding of infertility in this relatively educated population. With increasing demands on fertility services and limited public funds, better education is essential to ensure patients are fully informed with regard to their reproductive life planning.